Transforming industrial policy for the digital age production, territories and structural change - Patrizio Bianchi, Clemente Ruiz Durán, Sandrine Labory (Editors) (MA USA Edward Elgar Publishing, 2019)
"This book argues that digital globalization is inducing deep and productive transformations, making industrial policy necessary in order to reorientate development towards inclusive and more sustainable growth. The book also demonstrates that industrialization remains an important development process for emerging countries. Regarding the future of jobs, the authors show how the substitution of labour in automation is not inevitable since technology is also complementary to human capital. Policymakers should pay more attention to the new skills that will be required. A particular concern is the rapid change in technology and business compared to institutions which take time to adapt. Territories have an important role to play in order to speed-up institutional adaptation, providing they can act coherently with the other levels of government"--Publisher description.
Includes bibliographical references and index.
Keywords: Industrial policy